In vitro adherence of Candida albicans isolated from patients with chronic periodontitis - Machado, Adriana Gadotti [UNESP]; Komiyama, Edson Yukio [UNESP]; Santos, Silvana Soléo Ferreira Dos; Jorge, Antonio Olavo Cardoso [UNESP]; Brighenti, Fernanda Lourenção [UNESP]; Koga-ito, Cristiane Yumi [UNESP] (Faculdade De Odontologia De Bauru - USP, 2011)
Adherence is considered an extremely important virulence factor in yeast. OBJECTIVE: The aim of this study was to analyze the adherence to epithelial cells of C. albicans isolated from patients with chronic periodontitis in comparison to healthy patients. MATERIAL AND METHODS: Candida albicans cells isolated from individuals with chronic periodontitis (n=25) and healthy controls (n=25) were included in this study. Suspensions of C. albicans (10(6) cells/mL) and epithelial cells (10(5) cells/mL) were mixed and incubated at 37ºC for 1 h. The number of yeasts adhered to 25 epithelial cells was counted. RESULTS: The number of C. albicans cells adhered to epithelial cells was statistically higher in the chronic periodontitis group than in the control group (Student's t-test, p=0.000). CONCLUSION:The results of the present study suggest a higher Candida adherence of samples isolated from patients with chronic periodontitis.
Keywords: Candida albicans; Cell adhesion; Periodontitis; Virulence factors